2020
DOI: 10.3389/fphar.2020.00361
|View full text |Cite
|
Sign up to set email alerts
|

4β-Hydroxycholesterol Signals From the Liver to Regulate Peripheral Cholesterol Transporters

Abstract: Activation of pregnane X receptor (PXR) elevates circulating 4b-hydroxycholesterol (4bHC), an agonist of liver X receptor (LXR). PXR may also regulate 25-hydroxycholesterol and 27hydroxycholesterol. Our aim was to elucidate the roles of PXR and oxysterols in the regulation of cholesterol transporters. We measured oxysterols in serum of volunteers dosed with PXR agonist rifampicin 600 mg/day versus placebo for a week and analyzed the expression of cholesterol transporters in mononuclear cells. The effect of 4bH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…A recent publication by Salonurmi et al . ( 42 ) showed that 4β-HC induces cholesterol efflux from peripheral mononuclear cells in vivo via transcriptional upregulation of ABCA1 and concomitant suppression of influx transporters. In our hands, 4β-HC did not induce ABCA1 expression in primary hepatocytes ( supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication by Salonurmi et al . ( 42 ) showed that 4β-HC induces cholesterol efflux from peripheral mononuclear cells in vivo via transcriptional upregulation of ABCA1 and concomitant suppression of influx transporters. In our hands, 4β-HC did not induce ABCA1 expression in primary hepatocytes ( supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other oxysterols like 4-hydroxycholesterol, 20-( S )-hydroxycholesterol, 22-( S )-hydroxycholesterol, 24-hydroxycholesterol, 24-( S )-hydroxycholesterol, 25-hydroxycholesterol, 27-hydroxycholesterol, and cholesterol itself also induced ABCA1 / Abca1 mRNA 205 , 305 , 313 , 315 , 319 - 327 and ABCA1 protein levels. 321 , 328 The increase in ABCA1 protein was functionally confirmed by an enhanced cholesterol 305 , 306 , 313 , 315 , 318 and phospholipid efflux, 311 , 318 as well as reduced total cholesterol influx. 305 Specifically 22-( R )-hydroxycholesterol and cholesterol induced both LXRA/Lxra and LXRB/Lxrb .…”
Section: Part I: Status Quomentioning
confidence: 96%
“…22-( R )-hydroxycholesterol ( Figure 2 ) has been established as the natural gold standard for ABCA1/Abca1 induction through LXR activation, 122 , 205 , 249 , 252 , 259 , 262 - 264 , 268 , 277 , 278 , 305 - 315 while 9- cis retinoic acid ( Figure 2 ) became the natural gold standard for RXR activation. 122 , 245 , 249 , 259 , 262 , 264 , 277 , 278 , 309 , 311 , 313 , 316 The inducing effects were described both on ABCA1/Abca1 mRNA 122 , 205 , 252 , 263 , 264 , 305 , 307 - 311 , 313 , 315 - 317 and ABCA1 protein levels. 122 , 252 , 263 , 264 , 306 , 309 - 311 , 316 , 318 …”
Section: Part I: Status Quomentioning
confidence: 99%
“…We have recently demonstrated that 4βHC, through its LXR agonism, could be a link between PXR activation and HDL-C metabolism as it regulates the expression of cholesterol transporters in macrophages [ 67 ]. The expression and function of efflux transporter ATP-binding cassette transporter A1 (ABCA1) and ABCG1 were induced by 4βHC in vitro.…”
Section: Hdl Cholesterol Metabolism and The Pxr—4βhc Axismentioning
confidence: 99%
“…Both ABCA1 and ABCG1 are known transcriptional targets of LXR [ 58 ]. The efflux, facilitated by ApoAI as an acceptor for cholesterol, was augmented by 4βHC more than the efflux to HDL2 [ 67 ]. Furthermore, 4βHC incubation repressed the expression and function of influx transporter lectin-like oxidized LDL receptor-1 (LOX-1).…”
Section: Hdl Cholesterol Metabolism and The Pxr—4βhc Axismentioning
confidence: 99%